Setting the Well Path Direction with the Help of Rotary Steerable Systems - P. Lozhechko, V.; V. Ashcheulov, A.; I. Binder, Ya.; L. Gutnikov, A.; D. Zimin, R.; A. Sokolov, D. (International Journal of Engineering and Technology, 2018)
This article describes the main reasons for the emergence of directional drilling, technological advances in directional drilling and the prerequisites that led to the creation of rotary steerable systems, the history of the emergence of modern principles of curvature control of the well path, a comparative analysis of existing implementations of these principles and the main results of the development of the RUS220 rotary steerable system prototype. Based on the materials studied, the main configurable parameters are identified that define a specific concept, the tasks are formulated, choosing and justifying further research directions for developing the principles of trajectory curvature vector when drilling small diameter wells using rotary steerable systems.Â